Motivasi Guru Pustakawan: Studi Kasus di Sekolah Luar Biasa A Pembina Tingkat Nasional - Pangestu, Galih Gita; Rachman, Margareta Aulia (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2017)
This research presents about human resources at Special school of A Pembina Tingkat Nasional Lebak Bulus Jakarta. The purposes of this research are to describe the teacher-librarian motivation at the works and any factor affecting. A case study method is used in this qualitative research. The result shows that the motivation of teacher-librarian works based on his/her desire to make a better library. In addition, the factor which influence the motivation of teacher library based on achievements, acknowledgment, responsibility and their status.